ENRICHMENT OF LIPID PRODUCTION FROM CHLORELLA PYRENOIDOSA USING TOFU WASTE BY OPTIMIZING THE LEVEL OF DILUTION AND ACIDITY - Christopher Kioshi, Kevin
The tofu industry is one of Indonesia’s largest industrial scales, scaling up to 84.000 bussiness units. With this they create about 2610 kg of waste for every 80 kg of tofu produced. Tofu wastewater contains organic materials that consists of protein and lipid about 40 – 60% (226.06mg/L to 434.78 mg/L), carbohydrate (25%-50%), and fats (10%). This is more than enough nutrients to allow microalgae to grow. Microalgae is a species that can grow in three different mechanisms, these are heterotrophic, autotrophic, and mixotrophic. Heterotroph means that it can produce their own food in the absence of light and relies on a carbon source, such as sugars. Autotroph specifically photoautotroph refers to being able to produce food in the presence of light and carbon dioxide. Mixotroph is a combination of the two mechanisms where both the light and dark regime occurs. By limiting specific nutrients, microalgae can either cause in increase growth and increase lipid production. This research aims to use the microalgae Chlorella pyrenoidosa, we will analyze and optimize the biomass and lipid concentration using calculation of optical density of wavelength 680nm for biomass calculation and using the Bligh & Dryer method to extract lipid. Variation is done by diluting different concentrations of tofu wastewater at 10%, 15%, and 20% at pH 7.5 at constant ambient temperature in the presence of light to identify which amount of nutrient content suits for maximum biomass growth. After identifying optimal nutrient content, varying pH of 5, 6, 8, and 9 with the optimum dilution of tofu wastewater.